Purchase intentions for renewable energy in Polish households: an extended technology acceptance model approach - Siuda, Dagna; Grębosz-Krawczyk, Magdalena (Frontiers in Energy Research, 2025)
IntroductionDespite the presence of renewable energy appliances in the market for an extended period, they continue to be perceived as a relatively new technology. This perception may influence consumer adoption and the broader acceptance of renewable energy solutions.MethodsIn this study, the technology acceptance model (TAM) was applied to investigate individuals’ intention to use green energy sources. The TAM helps understand how users perceive and support new technologies. The survey was carried out in June 2024 on a sample of 580 Polish consumers using a self-administered questionnaire, employing a random selection method.ResultsThe results of structural equation modeling show a positive impact of Perceived Ease of Use and Perceived Usefulness, influenced by social factors, on Purchase Intention of green energy technology. Among these two variables, Perceived Usefulness influenced by social factors (PUS) had the more substantial effect.DiscussionOne key insight for producers, sellers of renewable energy systems, and policymakers is that potential users are primarily motivated by the Perceived Ease of Use of these systems.